Chlorophyll-a concentrations in the Arabian Gulf waters of arid region: A case study from the northern coast of Qatar - Sankaran Rajendran (14152830) (2022)
Remote sensing of spectrally active Chlorophyll-a (Chl-a) in the gulf water of an arid region is important to understand the spatial and temporal variations of phytoplankton and biomass in the water. This study characterizes the spectral absorption of Chl-a and detects and maps the Chl-a of Al Arish–Al Ghariyah coastal region of northern Qatar using the data of Hyperion of EO-1, MultiSpectral Instrument (MSI) of Sentinel-2, and Operational Land Imager (OLI) of Landsat-8 satellites. The study of image spectra of Chl-a of coastal water of the Al Ghariyah region using the Hyperion image showed spectral band absorptions near 450 and 475 nm in the blue region and around 640, 730, 760, and 830 nm in the red region. The analysis of Hyperion data using image spectra by linear spectral unmixing (LSU) method showed the occurrence of Chl-a in very shallow and shallow water. The mapping of Chl-a of the Al Arish–Al​ Ghariyah coastal region was carried out using MSI and OLI data by NDCI, 2BDA, 3BDA, and FLH violet algorithms, which showed the concentrations and distributions of the Chl-a in the region. The performance of the algorithms was studied using WorldView-3 data, which provided the R2 values of 60% and the best suitability of the NDCI algorithm and MSI data to map the concentration of Chl-a. All the results were validated using field measurements, in-situ measurements, and laboratory analyses of field samples. The measurements of Chl-a showed the occurrence of poor occurrence of Chl-a and confirmed the imagery results. The remote sensing results with physical and chemical parameters of water samples allowed us to assess Chl-a concentrations in the region. This study evaluates the sensor’s capability and applications of satellite data and algorithms to map concentrations of Chl-a in the Gulf waters of the arid region. Other Information Published in: Regional Studies in Marine Science License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.rsma.2022.102680